1999
DOI: 10.1128/aem.65.5.2072-2077.1999
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Choline and Glycine Betaine Uptake and Metabolism in the Family Rhizobiaceae and Their Roles in Osmoprotection

Abstract: The role of glycine betaine and choline in osmoprotection of various Rhizobium, Sinorhizobium,Mesorhizobium, Agrobacterium, andBradyrhizobium reference strains which display a large variation in salt tolerance was investigated. When externally provided, both compounds enhanced the growth of Rhizobium tropici,Sinorhizobium meliloti, Sinorhizobium fredii,Rhizobium galegae, Agrobacterium tumefaciens,Mesorhizobium loti, and Mesorhizobium huakuii, demonstrating their utilization as osmoprotectants. However, both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…Although minor Pcs activity was detected, it was found that SEMIA 6144 is incapable of incorporating [ 14 C]choline from the medium (data not shown). This is consistent with a previous study that had shown that all the rhizobial strains tested, except B. japonicum, possess a choline uptake activity and can use choline as a carbon, nitrogen and energy source for growth (Boncompagni et al, 1999).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Although minor Pcs activity was detected, it was found that SEMIA 6144 is incapable of incorporating [ 14 C]choline from the medium (data not shown). This is consistent with a previous study that had shown that all the rhizobial strains tested, except B. japonicum, possess a choline uptake activity and can use choline as a carbon, nitrogen and energy source for growth (Boncompagni et al, 1999).…”
Section: Resultssupporting
confidence: 93%
“…Recently, Hacker et al (2008) have reported the presence of multiple functional phospholipid N-methyltransferases (Pmts) exhibiting different substrate specificities in B. japonicum and proposed a model in which phosphatidylcholine biosynthesis is achieved mainly by the concerted action of PmtA and PmtX1. Although it has been reported that B. japonicum is unable to take up choline (Boncompagni et al, 1999), its genome contains a functional Pcs (Hacker et al, 2008) and some Pcs activity can be detected in cell extracts of B. japonicum (Martínez-Morales et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…The absence of a BetS like system in R. leguminosarum may be important in the sensitivity of this species to NaCl stress. This sensitivity of all three biovars of R. leguminosarum to NaCl stress and the inability of choline and glycine betaine to protect against it has been observed previously (Boncompagni et al, 1999). In this study a much wider range of compatible solutes were tested but again none were effective.…”
Section: Discussionsupporting
confidence: 77%
“…This is compatible with the idea that a moderately active PmtA is progressively taking over PC synthesis in vivo because choline becomes either unavailable in the Brucella vacuole or used for other purposes. Indeed, choline can be used to synthesize the osmoprotectant glycine betaine, and some α-2 Proteobacteria also use it as C and N source (Smith et al, 1988;Boncompagni et al, 1999). Again, the behaviour of the double mutant in mice is fully consistent with these possibilities and supports the interpretation that PC is necessary for B. abortus virulence.…”
Section: Discussionsupporting
confidence: 57%